METHODOLOGICAL FOUNDATIONS FOR THE ORGANIZATION OF INDEPENDENT EDUCATION OF STUDENTS ON THE BASIS OF ELECTRONIC PLATFORMS - Ismatovna, Asadova Yulduz (Journal of Higher Education and Academic Advancement, 2024)
The article is aimed at developing the literacy of the teaching staff and students of higher educational institutions on the use of information systems in the organization of independent study of students in higher educational institutions and contains useful information about the structure, capabilities, and practical application of the LMS Moodle platform. The LMS Moodle platform is an open electronic system that has been used by many universities around the world for many years. The system can be configured according to the specifics of education in each higher education institution, which makes it a user-friendly interface. This platform can be effectively used for a certain degree of automation of the educational process, especially in the organization of independent study of students. Currently, a credit-modular education system is being widely implemented in higher educational institutions of the country. The article provides illustrative examples of the application of many functions and procedures of the Moodle platform, wider use of the program's capabilities, especially the use of graphical capabilities when creating content. This article can be used by teachers, students, teachers and specialists of higher educational institutions.